Preschool in three cultures : Japan, China, and the United States - Tobin, Joseph Jay.; Wu, David Y. H.; Davidson, Dana H., 1949-; Hsueh, Yeh; Karasawa, Mayumi (New Haven, Connecticut : Yale University Press, 1989)
Published twenty years ago, the original Preschool in Three Cultures was a landmark in the study of education: a profoundly enlightening exploration of the different ways preschoolers are taught in China, Japan, and the United States. Here, lead author Joseph Tobin-along with new collaborators Yeh Hsueh and Mayumi Karasawa-revisits his original research to discover how two decades of globalization and sweeping social transformation have affected the way these three cultures educate and care for their youngest pupils. Putting their subjects' responses into historical perspective, Tobin, Hsueh, and Karasawa analyze the pressures put on schools to evolve and to stay the same, discuss how the teachers adapt to these demands, and examine the patterns and processes of continuity and change in each country. Featuring nearly one hundred stills from the videotapes, Preschool in Three Cultures Revisited artfully and insightfully illustrates the surprising, illuminating, and at times entertaining experiences of four-year-olds-and their teachers-on both sides of the Pacific.
Introduction Komatsudani: A Japanese Preschool Dong-feng: A Chinese Preschool St. Timothy's: An American Preschool A Comparative Perspective.
Includes bibliographical references (pages 249-258)
Index (pages 259-265)
2
CIU has obtained rights for you to copy and share this title in electronic or print format with students, faculty, and staff.
Keywords: Nursery schools -- Japan -- Case studies; Nursery schools -- China -- Case studies; Nursery schools -- United States -- Case studies; Educational anthropology; Nursery schools; Early Childhood Education; Case studies; Instructional and educational works